2020
DOI: 10.1115/1.4048797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clearance on the Performance of a Labyrinth Seal Under Wet-Gas Conditions

Abstract: please see the attachment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The same tendency is also presented in Ref. [22]. Moreover, the k and the C are the largest at C r = 0.1 mm.…”
Section: Dynamic Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…The same tendency is also presented in Ref. [22]. Moreover, the k and the C are the largest at C r = 0.1 mm.…”
Section: Dynamic Characteristicssupporting
confidence: 86%
“…The results showed that the whirl frequency ratio of smooth-stator/grooved-rotor seal is generally high, which means poorer stability characteristics. Zhang et al [22] measured the influence of clearance on the rotor performance of a labyrinth seal in wet-gas conditions. They discovered that small clearance obtained high critical speed for inlet liquid volume fraction from 12% to 15%.…”
Section: Introductionmentioning
confidence: 99%